Peran Agrowisata dalam Meningkatkan Perekonomian Lokal: Studi Kasus Agrowisata Purwosari, Kecamatan Mijen, Kota Semarang - Amalia, Novi Safitri; Ulya, Firla Himmatul; Safitri, Amalia; Nadhifah, Chusniatun; Amelia, Tria (CV.ITTC INDONESIA, 2025)
This study aims to analyze potential, development, innovations, as well as the social and economic impacts of the Purwosari Agrotourism on the surrounding community. Located in Semarang Regency, Purwosari Agrotourism combines agricultural activities with educational tourism. Since its establishment in 2016, the agrotourism site has experienced significant growth, with more than 50 types of crops being cultivated and the implementation of modern agricultural technology. Throught a qualitative approach involving direct observation and interviews, this study reveals that Purwosari Agrotourism has successfully increased local income and raised awareness about sustainable agriculture. However, challenges such as inadequate infrastructure and limited promotion still need to be addressed for further development.